Retrospective evaluation of costs associated with methyl bromide critical use exemptions for open field strawberries in California. Issue 2 (June 2014) - Wolverton, Ann
Abstract: Methyl bromide (MBr) has been widely used as a fumigant to control pests in the agricultural sector, but it is also an ozone depleting substance. After 2005, methyl bromide could only be produced when a critical use exemption was agreed to by the signatories to the Montreal Protocol. This paper examines how the EPA's ex ante cost analyses for open field fresh strawberries in California for the 2006–2010 seasons compare to an ex post assessment of costs. A key input into the ex ante cost analysis is the assumed yield loss associated with methyl bromide alternatives. The EPA used conservative assumptions given the wide range of estimates in the literature at the time, but it appears that a number of viable MBr alternatives – either new fumigants or new ways of applying existing fumigants – may have become available more quickly and resulted in lower yield loss than initially anticipated. Likewise, it appears that farmers who substituted away from methyl bromide did so without imposing large negative impacts on production in prime California strawberry growing areas. Ex post evaluation also confirms the effect of California regulatory restrictions in limiting the use of various economically competitive alternatives. It is worth noting that unanticipated complications after switching away from methyl bromide, such as new diseases, slowed the transition to MBr alternatives.